Rethinking Urban Decline in Post-COVID19: Bibliometric Analysis and Countermeasures - Jiazhen Zhang; Muxia Yao; Jeremy Cenci (Buildings, 2023)
Urban decline refers to the sustained deterioration of cities in terms of their economy, population, and social aspects. The outbreak of the Coronavirus Disease 2019 (COVID-19) pandemic in 2019 objectively affected the trajectory of this phenomenon. A comprehensive analysis of scientific research on urban decline and its practical implications was conducted using bibliometric methods, data acquired from 2019 to 2023 and the Web of Science. Since COVID-19, research on urban decline has been predominantly led by traditional developed countries such as the United States and England, with a high degree of regional collaboration. Keyword clusters have focused on urban regeneration, growth, decay, family planning, resource dependency theory, public art, etc. Keyword co-occurrence has focused on shrinking cities, gentrification policy, land use, etc. Based on previous analyses and the contemporary context, the intrinsic logic behind the urban decline in recent years can be summarized as inadequate economic development, lagging infrastructure construction, the siphoning effect of core regional cities, and unique institutional factors leading to specific urban decline patterns. Comprehensive urban recovery plans have been proposed, including reshaping urban spatial layouts and planning and strengthening strategies for social and economic revival, with correspondence-specific samples. Studying the impact of COVID-19 on urban decline from the perspectives of city development and strategies can help us better understand the repercussions of global health crises on cities, providing a more scientific basis for urban planning and management to build resilient, sustainable, and equitable cities.